Effect of different reducing agents on phase formation and transformation behaviour of Ni-Ti shape memory alloy - Mohd Zaki, Hafizah Hanim; Bahrudin, Nik Amnani; Abdullah, Jamaluddin; Sarifuddin, Norshahida (IOP, 2018)
In this study, NiTi synthesized via solid-state sintering from Ni-TiH2 powders in reducing environments using (i) CaH2 (ii) MgH2 and (iii) CaH2 and MgH2 as in situ reducing agent were investigated. The phase formation was characterized by means of scanning electron microscope (SEM), energy-dispersive spectroscope (EDS) and powder X-ray diffraction (XRD), while transformation behavior was analyzed using differential scanning calorimetry (DSC) measurement. Among these three reducing agents, synthesis in reducing environment using CaH2 as in situ reducing agent resulted in the formation of single phase NiTi with enthalpy change of 25-26 J/g, which is similar to melt-cast NiTi alloys. Specimens sintered in reducing environments using MgH2 and MgH2+CaH2 as in situ reducing agents have lower enthalpy change, ~16-21 J/g compared to CaH2. This work established the fact that, synthesis in different reducing environment appears to have profound effects on the phase formation and transformation behavior of NiTi.